Penerapan dan Integrasi Prinsip-Prinsip Hukum terhadap Penyelundupan Hukum yang Berlaku Dikontrak Dagang Internasional - Yulian Dwi Nurwanti; Adhy Nugraha; Bambang Tresno wahyudi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
A country in its efforts to prosper the people requires a lot of money. For this reason, financial resources are needed to finance the state, which come from Customs levies and other legal levies. Smuggling crime is a serious problem in the administration of the state economy, this is because if smuggling increases with various physical, or administrative forms, it will result in more money not being collected by a country, thus hampering the targets set by the state through customs levies which are expected to increase every year. Legal smuggling is an act that aims to avoid the application of national law so that the person concerned obtains a certain benefit according to his wishes. This smuggling consists of two types, namely physical smuggling and administrative smuggling. Legislation regarding smuggling offenses is contained in Law Number 17 of 2006 concerning Amendments to Law of the Republic of Indonesia Number 10 of 1995 concerning Customs. And the parties responsible and related to the field of customs and excise must be more selective in checking export and import goods entering or leaving Indonesia, because misuse of procedures or authority will have a major impact on state losses.